Identification and functional study of three nAChR regulators, ubiquilin‐1, PICK1, and CRELD2, in Locusta migratoria manilensis dorsal unpaired median neurons. Issue 3 (18th January 2019) - Yu, Na; Wang, Xin; Bao, Haibo; Liu, Zewen
Abstract: Insect nicotinic acetylcholine receptors (nAChRs) are not only important neurotransmitter receptors but also effective insecticide targets. The regulation of nAChRs has been mainly studied in vertebrates, especially in mammals. Here, two types of nAChRs were found present in the locust Locusta migratoria manilensis dorsal unpaired median (DUM) neurons, α‐bungarotoxin (α‐Bgt)‐sensitive nAChRs and α‐Bgt‐resistant nAChRs, responding to acetylcholine (ACh) at different concentrations. The homologs to three mammalian nAChR regulators, ubiquilin‐1, CRELD2 (cysteine‐rich with EFG‐like domain 2), and PICK1 (protein interacting with PRKCA 1), were characterized in L. migratoria, and their functions on regulating native nAChRs were investigated via RNAi followed by membrane potential measurement with DiBAC4 (3) and agonist‐evoked macroscopic current recording in cultured L. migratoria DUM neurons. Ubiquilin‐1 and PICK1 negatively regulated nAChRs because silencing of ubiquilin‐1 and PICK1 both resulted in increased membrane potential and increased inward currents in DUM neurons, while CRELD2 positively regulated nAChRs as decreased membrane potential and inward currents were observed in DUM neurons. In addition, ubiquilin‐1 regulated both α‐Bgt‐sensitive and α‐Bgt‐resistant types of nAChRs whereas PICK1 and CRELD2 regulated only the α‐Bgt‐resistant nAChRs. The present study broadened our understanding on the regulation of insect nAChRs and will benefit pest management given the important role of nAChRs in insect neurons and insecticide science. Open science badges: This article has received a badge for *Open Materials * because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : The nicotinic acetylcholine receptors (nAChRs) have been intensively studied for its importance in insecticide resistance. However, information about the regulation of nAChRs is limited in insects. We cloned and quantified three nAChR regulator genes, ubiquilin‐1, PICK1, and CRELD2, in Locusta migratoria manilensis . siRNA‐mediated RNAi of ubiquilin‐1 and PICK1 in DUM neurons both resulted in the observation of increased inward current which we proposed to be mostly because of the increased activity or availability of nAChRs. Knockdown of CRELD2 led to the opposite observation most likely because of the suppressed activity or availability of nAChRs. We think that these findings provide a new insight for the development of nicotinic cholinergic system‐based pest management strategy. Open Science: This manuscript was awarded with the Open Materials Badge For more information see:https://cos.io/our-services/open-science-badges/